The complete mitochondrial genome and phylogenetic analysis of the deep-sea limpet Bathyacmaea lactea. Issue 7 (3rd July 2021) - Liu, Yaran; Li, Yuli; Wang, Minxiao; Bao, Zhenmin; Wang, Shi
Abstract: The deep-sea limpet Bathyacmaea lactea, inhibited in cold seeps of the South China Sea, belongs to the most primitive gastropod groups, the Patellogastropoda (true limpets). Here, we report the complete mitochondrial genome of B. lactea, which is 18, 446 bp in length and contains 13 protein-coding genes, 2 rRNAs, and 22 tRNA genes. The mitochondrial genome of B. lactea enriches the molecular resources for further understanding deep-sea molluskan adaptation and Gastropoda evolution.